2017
DOI: 10.25258/ijcprr.v8i01.9089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respect for Patient's Rights from the Viewpoint of Hospitalized Surgical Patinents in Shohada Ashayer Hospital of Khorramabad City, Iran in 2015-2016

Abstract: One of the most important branches of medical science, until past time, law and consequently to medical ethics. Patients' satisfaction of their rights, one of the most important indicators of effectiveness, efficiency, productivity and quality of healthcare services. The goal of this study was to Check the Observance of the rights of patients in surgical patients admitted to Shohaday Ashayer hospital in 2015-2016 from the perspective of patients. This cross-sectional study included 800 patients admitted to Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on the results, they stated that having a supervisor can be effective in promoting the culture of reporting medical errors [ 42 ]. Errors in human action are inevitable and act as an integral part of human reality [ 17 , 19 ]. Even the most skilled experts may have MEs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results, they stated that having a supervisor can be effective in promoting the culture of reporting medical errors [ 42 ]. Errors in human action are inevitable and act as an integral part of human reality [ 17 , 19 ]. Even the most skilled experts may have MEs [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poorolajal et al, stated that people’s lack of attention to the importance of medical errors and the lack of an effective reporting system for medical errors, and emphasis on the person who commits the error, were the reasons for reluctance to report medical errors [ 46 ]. Developing a systematic approach to the culture of error reporting and active participation in staff and identifying and knowing the causes that lead to medical errors can be helpful [ 19 ]. Evidence has shown that an anonymous, non-punitive critical incident reporting system can act as a powerful tool to identify the majority of medical errors and risk factors and may help prevent preventable adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations